Foot and Mouth Disease vaccination stress on semen quality in Murrah bulls - MURUGAVEL, K; RAJASEKARAN, J; SUBRAMANIAN, A (The Indian Journal of Animal Reproduction, 2023)
Foot and Mouth Disease vaccination stress on semen quality in Murrah buffalo bulls as investigated in this study. No significant changewas recorded in the semen volume following FMD vaccination. However significant decrease in spermatozoa: concentration, initial motility, livesperm percent and significant increase in the percentage of total spermatozoa! abnormalitieswere noticed following FMD vaccination. Increased spermatozoa! abnormalities returns to pre-vaccination level significantly on eighth week post-vaccination.
Keywords: Foot and Mouth Disease; vaccination stress; semen quality; Murrah bulls